Страна встает со славою: Стихотворения / Б. П. Корнилов - Корнилов Б. П. (библиотека поэзии "Россия", 1976)
Экземпляры: (20190402) / Инвентарный номер: 2978 / Цена: 0.93 / Сис.шифр: Р2 / Авт.знак: К67 / ББК: Р2